Quality Assurance of Essential Primary Health Care Services at Primary Health Care Centers in AL-Najaf AL-Ashraf Governorate - Haider K. Al Jebore (Journal of Global Pharma Technology, 2018)
Objective(s): To determine the quality assurance for essential primary health care services in AL-Najaf AL-Ashraf Governorate, identify the relationships between the quality assurance for essential primary health care services and characteristics of the organizational system, client satisfaction, and provided service. Methodology: A descriptive study is conducted throughout the period of September 1st 2016 to August 3rd 2017. A simple random sample of (504) subjects is selected through the use of probability sampling approach. The sample is divided into three groups which include (18) directors of primary health care centers, (18) primary health care services providers, and (468) consumers. A simple random sample of (504) subjects is selected through the use of probability sampling approach. The sample is divided into three groups which include (18) directors of primary health care centers, (18) primary health care services providers, and (468) consumers. Data is collected through the utilization of constricted questionnaires and the interview technique as means of data collection and keeping records of all available contacts that facilitate the access to the study sample. Interviews are conducted with directors of primary health-care centers, consumers, and workforce. Each interview takes approximately (5-10) minutes. The data collection was carried out from March 25 to June 6 2017. Content validity of the instrument is determined through a panel of (15) experts, and reliability through a pilot study. The data are analyzed through the application of descriptive and inferential statistical analysis procedures. Conclusions: The findings of the present study indicate that the mean catchments population for PHC centers is high; shortages of the medical, medical assistants, and administration workforce. The nursing, medical assistants, and administration staff are poorly distributed, maternal and child health services including family planning and health education services are in critical level, consumers showed inadequate overall satisfaction with primary health care services. Recommendations: The study recommends that to increase the total number of PHC centers according to the numbers of consumers within area; collaboration and coordination should be initiated between Ministry of Health, Ministry of Higher Education and Educational agencies to establish planning system to provide PHC facilities with workforce needed according to the numbers of consumers within the area, taken into accounts national standards; provision of scientific booklet on standards operating procedures (SOPs) and guided by clear job description in all fields of primary health care service provision.Keywords: Quality Assurance, Primary Health Care Services, Primary Health Care Centers.